CR3 Engaged by PGL-I Triggers Syk-Calcineurin-NFATc to Rewire the Innate Immune Response in Leprosy - Doz-Deblauwe, Émilie; Carreras, Florence; Arbues, Ainhoa; Remot, Aude; Epardaud, Mathieu; Malaga, Wladimir; Mayau, Véronique; Prandi, Jacques; Astarie-Dequeker, Catherine; Guilhot, Christophe; Demangel, Caroline; Winter, Nathalie (Frontiers in Immunology, 2019)
Mycobacterium leprae, the causative agent of leprosy, is unique amongst human pathogens in its capacity to produce the virulence factor phenolic glycolipid (PGL)-1. In addition to mediating bacterial tropism for neurons, PGL-1 interacts with Complement Receptor (CR)3 on macrophages (MPs) to promote infection. We demonstrate here that PGL-1 binding to CR3 also enhances bacterial invasion of both polymorphonuclear neutrophils (PMNs) and dendritic cells (DCs). Moreover, in all cell types CR3 engagement by PGL-1 activates the Syk tyrosine kinase, inducing calcineurin-dependent nuclear translocation of the transcription factor NFATc. This selectively augments the production of IL-2 by DCs, IL-10 by PMNs and IL-1b by MPs. In intranasally-infected mice PGL-1 binding to CR3 heightens mycobacterial phagocytosis by lung PMNs and MPs, and stimulates NFATc-controlled production of Syk-dependent cytokines. Our study thus identifies the CR3-Syk-NFATc axis as a novel signaling pathway activated by PGL-1 in innate immune cells, rewiring host cytokine responses to M. leprae.